Green School-Based Early Childhood Education: A Case Study at Kindergarten in Palembang - Puspita, Bella; Murtopo, Ali; Dewi, Kurnia (GENIUS: Indonesian Journal of Early Childhood Education, 2024)
This study investigates the implementation of green school-based learning in early childhood education at a kindergarten in Palembang, focusing on identifying its supportive and inhibitive factors and exploring solutions to these challenges. Using a qualitative case study approach, data were collected through interviews, observations, and documentation. The findings reveal that gardening, waste management, and plant cultivation significantly enhance children's environmental awareness and responsibility. Key supportive factors include adequate facilities and enthusiastic participation from students and teachers. The program demonstrates the potential to foster sustainable behaviors, environmental ethics, and personal responsibility among young learners. This research emphasizes the importance of integrating nature-based learning into early childhood curricula to cultivate eco-conscious attitudes and sustainable practices from a young age.